Multi-bed patient room architectural evaluation - Evangelia Sklavou; Ioannis Tzouvadakis (Ene, 2016)
Introduction: Leveraging the physical environment's merits is crucial in healthcare settings towards fostering sustainable healing conditions. In the future, the need to retrofit hospitals already appears more probable than to build new facilities. In Greece, holistic healthcare architecture has significant potential and room to develop. Aim: The architectural research of multi-bed patient room environment. Method: A sample of multi-bed patient rooms of a Greek hospital was studied per architectural documentation and user evaluation survey. Beyond recording the existing situation and user experience, user group differences and the influence of window proximity were studied. The survey sample was based on convenience and comprised 160 patients and 136 visitors. Statistical analysis was performed in SPSS 20, using chi-square exact tests of independence. The chosen level of significance was p < 0.05. Results: Architectural documentation showed that the building morphology had a positive impact in patient rooms, with regard to sunlight penetration and view. Further solar daylight control was deemed necessary, to facilitate overall environmental comfort conditions. High spatial density and considerable disadvantages of the middle patient bed, compared to the one bedside the window and the one further in the back of the room, were also ascertained. User groups did not evaluate their surroundings significantly different, with the exception of ease of access to the view. Window proximity influenced both patients and visitors in evaluating ease of access to the view and visual discomfort. Patients were further affected on window size evaluation and visitors on view related aspects. Conclusions: Synergy between building form and function contributes in creating holistic sustainable healing environments. User evaluation can deviate from objective documentation. Patients and visitors experienced the patient room in a similar manner. The middle bed was ascertained to have significant disadvantages. Notwithstanding specific particularities and needs, bed reduction should be considered.